A case report revealing acute onset psychosis and cognitive impairment as primary manifestation in relapsing‐remitting multiple sclerosis. Issue 5 (4th March 2020) - Nandy, Anirban; Nielsen, Michael; Hilt, Claudia; Mogensen, Poul Henning; Yavarian, Yousef
Abstract: Acute psychosis and cognitive impairment is a significant problem in RRMS. As it concerns in relatively young age group, our case report underscores the importance of early recognition which could impose diagnostic challenge in multiple sclerosis. Abstract : Acute psychosis and cognitive impairment is a significant problem in RRMS. As it concerns in relatively young age group, our case report underscores the importance of early recognition which could impose diagnostic challenge in multiple sclerosis